Human Leukocyte Antigen-A, B, C, DRB1, and DQB1 Allele and Haplotype Frequencies in a Subset of 237 Donors in the South African Bone Marrow Registry. (23rd April 2018) - Tshabalala, Mqondisi; Ingram, Charlotte; Schlaphoff, Terry; Borrill, Veronica; Christoffels, Alan; Pepper, Michael S.
Abstract : Human leukocyte antigen- (HLA-) A, HLA-B, HLA-C, HLA-DRB1, and HLA-DQB1 allele and haplotype frequencies were studied in a subset of 237 volunteer bone marrow donors registered at the South African Bone Marrow Registry (SABMR). Hapl-o-Mat software was used to compute allele and haplotype frequencies from individuals typed at various resolutions, with some alleles in multiple allele code (MAC) format. Four hundred and thirty-eight HLA-A, 235 HLA-B, 234 HLA-DRB1, 41 HLA-DQB1, and 29 HLA-C alleles are reported. The most frequent alleles were A∗ 02:02g (0.096), B∗ 07:02g (0.082), C∗ 07:02g (0.180), DQB1∗ 06:02 (0.157), and DRB1∗ 15:01 (0.072). The most common haplotype was A∗ 03:01g B∗ 07:02g C∗ 07:02g DQB1∗ 06:02 DRB1∗ 15:01 (0.067), which has also been reported in other populations. Deviations from Hardy-Weinberg equilibrium were observed in A, B, and DRB1 loci, with C DQB1 being the only locus pair in linkage disequilibrium. This study describes allele and haplotype frequencies from a subset of donors registered at SABMR, the only active bone marrow donor registry in Africa. Although the sample size was small, our results form a key resource for future population studies, disease association studies, and donor recruitment strategies.